Enhancing homebound instruction: current status and potential of telepresence technology. Issue 2 (15th March 2023) - Rosenthal, Eliana; Franklin Gillette, Sara R.; Nelson, Amanda K.; Dennis, Minyi Shih; DuPaul, George J.
ABSTRACT: When a student is homebound from school, they miss out on beneficial classroom experiences. One way to keep homebound students connected is through the use of telepresence technology. However, the existing literature has not been systematically reviewed to address important variables related to successful implementation. The authors conducted a systematic literature review on the use of telepresence technology for homebound K–12 students prior to the Covid-19 pandemic. Twelve articles published between 1990 and 2020 were included. Research on telepresence technology in the classroom is variable regarding outcomes studied and methodologies. Anecdotal data revealed that the use of telepresence technology increased homebound students' academic, social engagement and comfort. Implications for practitioners include feasibility of implementation of telepresence technology for students unable to physically attend classes and guidance in team structure necessary to successfully utilise telepresence. Increased funding allocated to controlled research and necessary infrastructure is essential for successful school-based implementation of telepresence technology.